Extended porphyrinoid chromophores: heteroporphyrins fused to phenanthrene and acenaphthylene. (5th November 2021) - Lash, Timothy D.; Rauen, Patrick J.
Abstract: Fusion of aromatic subunits onto porphyrin chromophores produces variable results and in some cases only minor bathochromic shifts are observed. In order to extend these observations, a series of oxa-, thia- and selenaporphyrins with fused acenaphthylene or phenanthrene units have been synthesized. Phenanthro[5, 6- b ]porphyrins were previously prepared via conventional '2 + 2' MacDonald condensations, but a more versatile '3 + 1' synthesis is now reported. Phenanthrotripyrranes reacted with a pyrrole dialdehyde in the presence of trifluoroacetic acid, followed by an oxidation step, to give phenanthroporphyrins. However, this chemistry initially gave products that were contaminated with isomeric impurities. Fortunately, good yields of isomerically pure phenanthroporphyrins were obtained when the reactions were carried out under relatively concentrated conditions, and a diphenanthroporphyrin was also obtained using this strategy. An alternative '3 + 1' synthesis was performed where a phenanthropyrrole dialdehyde was condensed with a tripyrrane and this also afforded a phenanthroporphyrin in good yields. Furan, thiophene and selenophene dialdehydes similarly reacted with phenanthro- and acenaphthotripyrranes to give a series of heteroporphyrins with fused phenanthrene and acenaphthylene rings. All of these porphyrinoids retained highly diatropic characteristics. As is the case for tetrapyrrolic porphyrins, the presence of a fused acenaphthylene unit leads to highly modified UV–vis spectra with multiple Soret bands and relatively strong Q bands above 650 nm. However, the longest wavelength absorptions for the acenaphthylene series were only red shifted by 12–15 nm compared to the phenanthrene-fused heteroporphyrin series, which is a somewhat reduced effect compared to previously reported phenanthroporphyrins and acenaphthoporphyrins. Nevertheless, the combined effects of core modification and acenaphthylene ring fusion affords potentially valuable strongly red shifted absorption bands between 677 and 684 nm. Graphical abstract: Image 1